The ban on gaming consoles in China: protecting national culture, morals, and industry within an international regulatory framework - Liboriussen, Bjarke; White, Andrew; Wang, Dan (Routledge, 2017)
From its ‘opening up’ policy in 19781 to the present day, China’s rapid economic growth has not only lifted hundreds of millions of its citizens out of poverty and made many extremely rich, but it has also been the catalyst for immense social transformation. In this chapter, we explore the tension between 1) Chinese policymakers’ desire for the wealth that access to global markets gives its citizens; and 2) the challenges to Chinese cultural and traditional ideas about morality that this social transformation brings in its wake. Our investigation focuses primarily on one particular case that exemplifes this tension: the Chinese government’s 2000 to 2014 ban on the importation of foreign-made video game consoles. We frst situate the ban within the context of China’s international commitments to ‘free trade’ and then consider the arguments made for exempting media content from such commitments. Here, the Chinese leadership’s ambiguous stance toward Western infuence is an important policy-shaping factor. For the second half, we zoom in on the policy document installing the de facto ban on consoles. Here policymakers frame the ban as a way of curbing the negative infuence of wangbas—Internet cafes—on China’s youth. We discuss whether such a move actually resonated with the public and to what extent public concerns were constructed rather than refected by the media. Although a critical approach to video game policy should remain skeptical of the motivations underlying policy, it also needs to acknowledge the possibility that policy responds to actual public concerns, even in a one-party state.